Strategy for the quality control of herbal preparations made of Sarcocephalus latifolius: Development and validation of a UHPLC‐PDA method for quantification of angustoline and strictosamide and chemical profiling using LC‐QToF. Issue 1 (25th October 2022) - Tittikpina, Nassifatou Koko; Katragunta, Kumar; Avula, Bharathi; Ali, Zulfiqar; Khan, Ikhlas A.
Abstract: Introduction: Sarcocephalus latifolius is one of the most used plants in West African traditional medicine to treat malaria. Objective: The aim is to establish a strategy to control the quality of herbal preparations made from S. latifolius . Method: A UHPLC‐PDA method was developed for the determination and quantification of the two main bioactive compounds (angustoline and strictosamide) in various parts of the plant. Additionally, an LC‐QToF with electrospray ionization method is described for the identification and confirmation of compounds in samples of different parts of the plant. Results: With the UHPLC‐PDA method, separation was achieved within 5 min using a C18 column stationary phase at a temperature of 45°C and a gradient system with a mobile phase of water and acetonitrile, both containing 0.1% formic acid. The method was validated for linearity, accuracy, precision (repeatability and intermediate precision), limit of detection (LOD), and limit of quantification (LOQ). The LOD and LOQ of angustoline were found to be 0.3 and 0.8 μg/ml, respectively, and those of strictosamide were found to be 0.1 and 0.3 μg/ml, respectively. Using the LC‐QToF method, 90 secondary metabolites, including four isolated compounds from the plant's roots, were identified from leaf, bark, and root samples of S. latifolius . Conclusion: This work is the first to propose a strategy to control the quality of herbal preparations made from S. latifolius . The developed method allows the quantification of the main bioactive compounds and the established chemical profile allows to distinguish the plant from any other species. Abstract : Sarcocephalus latifolius is one of the most used plants in West African traditional medicine to treat malaria. A strategy was designed to control the quality of herbal preparations made from the plant: a UHPLC‐PDA method was developed for the determination and quantification of the two main bioactive compounds (angustoline and strictosamide) in various parts of the plant, and an LC‐QToF with electrospray ionization method is described for the identification and confirmation of 90 secondary metabolites in the plant's parts.